ANALYSIS DEVELOPMENT OF COMPUTERIZATION ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION USING TECHNOLOGY ACCEPTANCE MODEL (TAM) - siti rahmi (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
This study aims to analyze the influence of infrastructure, human resources, costs, usefulness perceptions, and perceived ease of implementation of computerized accounting information systems. The population in this study were employees of the Padang Primary Tax Service Office. Based on the purposive sampling method, this study uses a sample of 47 respondents who work as employees of the accounting and finance department. For the dependent variable (y) of this study is the implementation of computerized accounting information systems. While for the independent variables are infrastructure (x1), human resources (x2), costs (x3), perceived usefulness (x4), and perceived ease (x5). The method used is quantitative research methods. This study uses primary data from the questionnaire. Data were analyzed using multiple regression analysis which was processed through IBM SPSS Statistic software ver 20. The results of this study indicate that human resources, perceived usefulness and perceived convenience have a positive and significant effect on the implementation of computerized accounting information systems. But infrastructure and costs do not affect the implementation of computerized accounting information systems. Keywords: Infrastructure, Human Resources, Costs, Perception of Use, Perception of Convenience, Implementation of Computerized Accounting Information Systems